A Literature Review on the Role of Family Medicine in the Early Detection and Management of Type 2 Diabetes - Alnissayan, Abdullah Ibrahim Abdullah; Almasaari, Fatmah Hadi; Alothman, Noura Hamed; Almalki, Badria Abdullah; Alhajri, Shikah Mohammed S; Alamri, Osamah Abdullah; Alshehri, Khaled Mohammed; Bukhari, Khuloud Omar; Alshamrani, Alanoud Abdulrahman; Alhabib, Ali Tareq; Albarakat, Mohammed Abdulaziz; Alshahrani, Amani Thamer (Journal of Posthumanism, 2024)
This systematic literature review examines the central role of family medicine in the early diagnosis and management of type 2 diabetes mellitus (T2DM). As the incidence of diabetes continues to increase globally, family medicine physicians remain the first point of contact for screening, diagnosis, and ongoing management of the chronic condition. This literature review synthesizes the latest evidence regarding screening methods, diagnostic techniques, lifestyle changes, pharmacological management, and care coordination strategies employed within family medicine clinics. The evidence finds that family physicians are optimally positioned for full-range diabetes care through their longitudinal patient connections, systems-thinking approach toward health, and community-oriented locations for practice. Salient findings emphasize the effectiveness of opportunistic screening, systematic lifestyle intervention programs, individualized pharmacotherapy, and multidisciplinary care coordination for superior outcomes for diabetes. Despite existing limitations ranging from barriers of time, resources, and noncompliance among patients, family medicine remains an essential platform for reducing the complications of diabetes and overall quality-of-life improvement among diabetes patients with T2DM. The literature review provides evidence-based recommendations for the enhancement of diabetes delivery within family medicine clinics and implications for further studies and support for implementation.